ChemInform Abstract: A Novel Visible Light‐Driven Silver Isocyanate Photocatalyst: Superior Stability Enhanced by Intrinsic Resonance Effect. Issue 5 (January 2016) - Fan, Shuo; Chen, Gang; Li, Chunmei; Lv, Chade; Han, Zhonghui; Rao, Jiancun; Hu, Yidong; Zhang, Congmin
Abstract: AgNCO is precipitated from an aqueous urea solution of AgNO3 (2 h, darkness).